2013
DOI: 10.1007/s00265-013-1654-y
|View full text |Cite
|
Sign up to set email alerts
|

Foreign egg retention by avian hosts in repeated brood parasitism: why do rejecters accept?

Abstract: Great reed warblers (Acrocephalus arundinaceus)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Furthermore, egg discrimination can also be influenced by a variety of other effects including egg arrangement (Polaciková et al 2013;Hanley et al 2015), nesting stage (Moskát et al 2014b), and the flushing of host parents (Hanley et al 2015). Our study also has implications for understanding the difference in threshold of releasing behavior among different cognitive mechanisms, which has rarely been demonstrated before.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, egg discrimination can also be influenced by a variety of other effects including egg arrangement (Polaciková et al 2013;Hanley et al 2015), nesting stage (Moskát et al 2014b), and the flushing of host parents (Hanley et al 2015). Our study also has implications for understanding the difference in threshold of releasing behavior among different cognitive mechanisms, which has rarely been demonstrated before.…”
Section: Discussionmentioning
confidence: 79%
“…; Moskát et al. ). Recent studies have confirmed the most prevalent prediction for the evolution of parasitic egg colour and pattern mimicry, initially tested by human observers (Davies ), that less mimetic eggs, when seen by the avian eye, are rejected more often (Cassey et al.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, eggshell coloration may result in crypsis or mimetism; cryptic eggs can remain undetected by predators, whereas brood parasites may mimic the coloration of host eggs (Kilner, 2006; Sullivan et al, 2003). Another important example is the nest parasite arms race model, where egg colour may help parents to identify their own eggs in species exposed to brood parasites (Feeney et al, 2016; Medina et al, 2016; Moskát et al, 2014). Additionally, a blue egg shell has been proposed to be a sexually selected signal of mating status that may induce a higher allocation of paternal care (Moreno & Osorno, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In cuckoos, egg shell colour is transmitted either cytoplasmatically (mitochondrion) or by the sex chromosome (W). This ensures that females resemble their hosts in egg colour (Feeney et al, 2016; Medina et al, 2016; Moskát et al, 2014). These studies have shown that the genetic mechanism underlying eggshell colour in birds is quite complex, and further insights regarding the molecular basis of avian eggshell colour need to be obtained to understand the evolution of avian eggshell colour.…”
Section: Introductionmentioning
confidence: 99%